ANALYSING THE ROLE AND MEANING OF DOWRY IN GLOBAL WEDDING TRADITIONS - Idris Siregar; Annisa Khumairoh Riadi; Xananta Zeres Ha'gai Br. Sembiring (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2024)
The purpose of this research is to find out what types of goods can be used as dowry in marriage. This research is a type of library research or literature study, which involves collecting, reading, recording, and processing data from various literature sources such as books, magazines, and others. The results show that dowry in Islam is an obligatory gift from the husband to the wife as part of the marriage contract, which has symbolic and material values. The form of dowry is very diverse and can be in the form of cash, jewellery, electronic or household items, land or property, livestock, education and services, religious travel expenses, and traditional or cultural items. This flexibility in the form of dowry allows for adjustments to economic conditions, culture, and the agreement of both parties. The most important thing is that the dowry is given with sincerity, fulfils the requirements of Islamic law, and reflects the husband's commitment and responsibility in building a household. Dowry is not just a material gift, but also a symbol of the husband's love, respect and seriousness in marriage.